2005
DOI: 10.17796/jcpd.29.4.n80t77w625118k73
|View full text |Cite
|
Sign up to set email alerts
|

Success of mineral trioxide aggregate in pulpotomized primary molars

Abstract: The aim of the present study was to compare, clinically and radiographically, the mineral trioxide aggregate (MTA) to formocresol (FC) when used as medicaments in pulpotomized vital human primary molars. METHODS: The sample consisted of 120 primary molars, all teeth were treated with the same conventional pulpotomy technique. Sixty molars received FC and 60 received MTA throughout a random selection technique. RESULTS: At the end of 24-month evaluation period, 74 molars (36 FC, 38 MTA) were available for clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
97
3
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 1 publication
9
97
3
8
Order By: Relevance
“…Farsi et al 21 reported a signifi cant dif ference between the two groups (MTA and FC pulpotomies in primary molars) after 24 months of radiographic evalu ation, but the results of this study were study, MTA showed a higher (though not statistically significant) long-term clini cal and radiographic success rate than formocresol. 22 In spite of the similarity of success rates of FC and MTA in this study, one clinical disadvantage of MTA compared to FC is the fact that the tooth has to be restored after 24 hours to allow time for the MTA to set.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…Farsi et al 21 reported a signifi cant dif ference between the two groups (MTA and FC pulpotomies in primary molars) after 24 months of radiographic evalu ation, but the results of this study were study, MTA showed a higher (though not statistically significant) long-term clini cal and radiographic success rate than formocresol. 22 In spite of the similarity of success rates of FC and MTA in this study, one clinical disadvantage of MTA compared to FC is the fact that the tooth has to be restored after 24 hours to allow time for the MTA to set.…”
Section: Discussioncontrasting
confidence: 65%
“…MTA has been proposed as a poten tial medicament for various pulpal pro cedures in permanent teeth, eg pulp capping, apexification, repair of root perforations etc, and has had successful results. [20][21][22][23][24] With due attention to the bio compatibility and biological seal of MTA, several studies have been performed to evaluate its efficacy as a pulpotomy medicament in primary molars. [8][9][10]13,21 Eidelman et al 8 showed MTA pulpoto mies in primary molars that were followed up for 6-30 months were clinically and radiographically successful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7] Medicaments applied to radicular pulp tissue after pulpotomy have included formocresol, 1,3,4 ferric sulphate, 3,4 calcium hydroxide 4 and mineral trioxide aggregate (MTA). 1,[8][9][10][11][12][13][14] Objective This study compared the clinical and radiographic effectiveness of mineral trioxide aggregate (MTA) and Portland cement (PC) as pulp dressing agents in carious primary teeth. Methodology Thirty carious primary mandibular molars of children aged 5-9 years old were randomly assigned to MTA or PC groups, and treated by a conventional pulpotomy technique.…”
Section: Introductionmentioning
confidence: 99%